2020
DOI: 10.1002/advs.202002397
|View full text |Cite
|
Sign up to set email alerts
|

Prototypic Lightweight Alloy Design for Stellar‐Radiation Environments

Abstract: The existing literature data shows that conventional aluminium alloys may not be suitable for use in stellar-radiation environments as their hardening phases are prone to dissolve upon exposure to energetic irradiation, resulting in alloy softening which may reduce the lifetime of such materials impairing future human-based space missions. The innovative methodology of crossover alloying is herein used to synthesize an aluminium alloy with a radiation resistant hardening phase. This alloy-a crossover of 5xxx a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 97 publications
(208 reference statements)
0
14
1
Order By: Relevance
“…The harsh environment including radiation and thermal cycling always has a negative effect on the structure and performance of the exposed materials in space. [ 102 ] The effect of atomic oxygen erosion is the primary cause of material degradation, which can lead to a decrease in mechanical, optical, and electrical properties for printed electronics. Ouchen et al studied the effects of atmosphere in a low Earth orbit, particularly atomic oxygen, on printed metal traces through direct exposure for 6 months aboard the ISS; they found that the atomic oxygen harmed the unpassivated printed materials, as shown in Figure a.…”
Section: Survivability For Printed Electronics In Spacementioning
confidence: 99%
“…The harsh environment including radiation and thermal cycling always has a negative effect on the structure and performance of the exposed materials in space. [ 102 ] The effect of atomic oxygen erosion is the primary cause of material degradation, which can lead to a decrease in mechanical, optical, and electrical properties for printed electronics. Ouchen et al studied the effects of atmosphere in a low Earth orbit, particularly atomic oxygen, on printed metal traces through direct exposure for 6 months aboard the ISS; they found that the atomic oxygen harmed the unpassivated printed materials, as shown in Figure a.…”
Section: Survivability For Printed Electronics In Spacementioning
confidence: 99%
“…The adventure of humans in space is mainly permitted through the knowledge acquired by an ancient science: the metallurgy. The role of this science in the human-based exploration of space consists in the design and evaluation of the applicability of new materials for spacecrafts, satellites and space probes within the harsh environment of the space (1,2,3). The knowledge accumulated over 70 years on multinational space programs allowed the elaboration of a current list of materials' requirements for application in extraterrestrial environments, considering the multiple degradation mechanisms that may operate synergistically while in-service in space (2, 3): (i) high strength-to-weight ratio (4, 5, 6, 7), (ii) excellent thermal performance in a broader temperature range whilst in vacuum (8,9,10,6,7,11,12), (iii) high corrosion resistance to active monoatomic species (e.g.…”
mentioning
confidence: 99%
“…The knowledge accumulated over 70 years on multinational space programs allowed the elaboration of a current list of materials' requirements for application in extraterrestrial environments, considering the multiple degradation mechanisms that may operate synergistically while in-service in space (2, 3): (i) high strength-to-weight ratio (4, 5, 6, 7), (ii) excellent thermal performance in a broader temperature range whilst in vacuum (8,9,10,6,7,11,12), (iii) high corrosion resistance to active monoatomic species (e.g. O) and to ionizing plasma (13,14,15,16), (iv) easy manufacturability and repairability (17,18), (v) costs (19,20), and (vi) high radiation tolerance (1,2,21,3). As a limiting factor, the first requirement calls for materials that are inherently lightweight as this is intended to minimize payload, fuel demands and low production costs.…”
mentioning
confidence: 99%
See 2 more Smart Citations